(untitled) (CIPEEX, 2024)
KNOWLEDGE ABOUT MEDICINAL PLANTS IS ANCIENT, THEY WERE THE FIRST RESOURCES TO BE USED BY MEN FOR THERAPEUTIC PURPOSES, BEING ENJOYED IN COUNTLESS WAYS AND INTENTIONS. IT BECOMES POSSIBLE DUE TO THE SUBSTANCES FOUND IN THEM HAVING PHARMACOLOGICAL PROPERTIES AND ACTIONS THAT HELP IN THE PREVENTION, TREATMENT AND EVEN CURE OF SOME DISEASES. THIS IS A LITERATURE REVIEW STUDY, OF THE NARRATIVE TYPE, AND QUALITATIVE METHOD. IT AIMS TO DEMONSTRATE HEALING PROPERTIES OF MEDICINAL PLANTS IN ORDER TO RESCUE AND APPROPRIATE POPULAR KNOWLEDGE FOR THE SAFE, APPROPRIATE AND EFFICIENT USE OF FOUR SELECTED SPECIES. WE SEEK SCIENTIFIC BASIS ON THE TOPIC IN QUESTION, THROUGH ONLINE ACCESS TO DATABASES: SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO), LATIN AMERICAN AND CARIBBEAN LITERATURE IN HEALTH SCIENCES (LILACS), VIRTUAL HEALTH LIBRARY (VHL ) AND PUBMED. THE RESULTS FOUND RELATED TO THE USE OF MEDICINAL PLANTS WERE SOMEWHAT SATISFACTORY, AS THEY SHOWED THAT THEY ARE USED AS A THERAPEUTIC ALTERNATIVE FOR VARIOUS PATHOLOGIES. THIS WAS POSSIBLE WITH THE EMERGENCE AND EVOLUTION OF MODERN CHEMISTRY IN ASSOCIATION WITH THE KNOWLEDGE AND EXPERIMENTS OF ANCIENT PRACTICES IN THE DEVELOPMENT OF NEW AND DIVERSE DRUGS AND HERBAL MEDICINES. THIS PRACTICE, WHICH ORIGINATED IN THE BEGINNING, ARRIVED AND CONTINUED TO TRANSPOSE NEW CULTURAL DIMENSIONS. THEREFORE, THE SAFE USE OF MEDICINAL PLANTS OFFERS SEVERAL BENEFITS TO SOCIETY IN GENERAL. STUDIES CARRIED OUT ON ITS PROPERTIES AND CHEMICAL COMPOSITION ARE INCREASINGLY GAINING PROMINENCE AND SPACE IN THE INDUSTRIAL SECTOR, MAINLY IN THE PRODUCTION OF NEW MEDICINAL FORMULAS, USING PRESERVED ACTIVE INGREDIENTS. THUS, WITH THE PRESENT GROWTH OF KNOWLEDGE ABOUT PLANTS, ACQUIRE SOCIAL STATUS AND GREAT ECONOMIC IMPORTANCE. AMONG THEIR DIVERSE MEDICINAL USES, FOUR SPECIES WERE SELECTED THAT PRESENT DIFFERENT ACTIONS, NAMELY ERVA DE SANTA MARIA, HIBISCUS, SANGRA D€™GUA AND SUCUPIRA. IN WHICH, THE SCIENTIFIC AND POPULAR NAME, FAMILY, PARTS USED, INDICATION, WAY OF ACTING ON THE HUMAN BODY AND CONTRAINDICATION WERE DESCRIBED. FACED WITH THIS NEW ERA IN THE USE OF MEDICINAL PLANTS, THE ALERT MODE IS ACTIVATED REGARDING THE DISORDERED AND UNRESTRAINED USE OF THE VARIOUS EXISTING SPICES. BECAUSE THE INDISCRIMINATE USE OF THESE FOR MEDICINAL PURPOSES CAN POSE INHERENT RISKS TO HEALTH, PLANTS HEAL, HOWEVER, WHEN USED INCORRECTLY IT CAN BRING DANGERS AND EVEN LEAD TO DEATH. IT IS CONCLUDED THAT THE RISKS OF ADVERSE EVENTS DUE TO THE USE OF THESE PLANTS ARE LOWER, BUT NOT NON-EXISTENT, WHICH IS WHY IT IS RECOMMENDED TO SEEK OUT A QUALIFIED AND QUALIFIED PROFESSIONAL FOR BETTER GUIDANCE.